PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN DAN DAMPAKNYA TERHADAP COST OF EQUITY CAPITAL. (Studi Pada Emiten Manufaktur Di Bursa Efek Indonesia) - Elviza, Elviza (Fakultas Ekonomi Universitas Muhammadiyah Aceh, 2011)
ABSTRACT The purpose of this study was to examine and analyze the influence of institutional ownership and managerial ownership on firm value and its impact on the cost of equity capital either partially or simultaneously at the Stock Exchange listed companies manufacturing in Indonesia. This type of research is verification research with census method. The population of this study is that all manufacturing companies in Indonesia Stock Exchange that owns shares of managerial and institutional. Having selected the target population totaled 59 issuers. The analytical method used was path analysis (path analysis). Data used in this research is secondary data, obtained from audited financial statements for the fiscal year ended December 31, 2005 and as of December 31, 2008, and the stock price data during the observation period, issued by manufacturing companies and published by the Reference Center Capital Markets (PRPM) found on the Indonesian Stock Exchange (BEI). The results of this study indicate that, (1) institutional ownership and managerial ownership simultaneously affect firm value, (2) institutional ownership, managerial ownership and firm value simultaneously affect the cost of equity capital (3) Institutional Ownership partially give effect weak value of the firm (4) Managerial ownership partially provide a weak effect on the value of the firm (5) Institutional Ownership partially affect the cost of equity capital (6) Managerial ownership partially affect the cost of equity capital (7) value company partially affect the cost of equity capital. Keywords: institutional ownership, managerial ownership, corporate value and cost of equity capital. DAFTAR KEPUSTAKAAN Ainun dan Fuad. 2000. “Analisis Hubungan Kelengkapan Pengungkapan Laporan Keuangan dengan Struktur Modal dan Tipe Kepemilikan Perusahaan”, Jurnal Ekonomi dan Bisnis Indonesia, Vol. 15, No.1: 5-7 Ani dan Juniarti. 2003. “Pengaruh kualitas Disclosure terhadap Biaya Hutang” Simposium Nasional Akuntansi VI: 2-3 Amurwani, Aniek. 2006. Pengaruh Luas Pengungkapan Sukarela dan Asimetri Informasi terhadap Cost Of Equity Capital. Skripsi, Universitas Islam Indonesia, Jogjakarta. Arifin, zainul, agus (2008) Modul manajemen keuangan. Biaya Modal (cost of capital) Botosan, C.A.,1997, “Disclosure Level and the Cost of Equity Capital”, The Accounting Review, Vol.72, No.3:323-349. Claessens, S.,Djankov, and L.H.P. Lang, 2000a. The Separation of Ownership and Control in East Asian Corporation. Journal of Financial Economics 58: 81-112 Diamond, D., and R. Verreecchia, 1991, “Disclosure, Liquidity and the Cost of Equity capital”, The Journal of Finance (September): 1325-1360. Demsetz, Harold, and Kenneth Lehn, 1985. The Structure of Corporate Ownership: Causes and Consequences. Journal of Political Economy, Vol. 93, No. 6, December; 1155-1177. Fitriany, 2001, “Signifikansi Perbedaan Tingkat Kelengkapan Pengungkapan Wajib dan Sukarela pada Laporan Keuangan Perusahaan Publik yang Terdaftar di Bursa Efek Jakarta”, Simposium Nasional Akuntansi IV, Sesi 3:5-7 Firmantyas,Putri Imanda, dan Nasir Muhammad. 2006. Analisis persamaan simultan kepemilikan Manajerial, Kepemilikan Institusional, risiko, kebijakan hutang dan kebijakan deviden dalam perspektif teori keagenan. Simposium Nasional Akuntansi Padang. Gulo, Yamotuho, 2000, “Analisis Efek Luas Pengungkapan Sukarela dalam Laporan Tahunan terhadap Cost of Equity Capital Perusahaan”, Jurnal Bisnis dan Akuntansi, vol.2, No.1:12-16. Gomes, A., G. Gorton, and L. Madureira, 2005. SEC Regulation Fair Disclosure, Information, and the Cost of Capital. Working Paper, http://papers. ssrn.com/sol3/papers.cfm?abstract_id=529162, September: 42-57. Gujarati, 1997, “Ekonometrika Dasar”, Edisi Kelima, Jakarta : Erlangga. Hadi, Waskito.2010. Pengaruh Likuiditas dengan rasio lancar dan Leverage terhadap kemandirian daerah. Thesis program magister ilmu akuntansi Unsyiah. Holderness, C.G., dan Sheehan, D.P. 1988. The role of majority shareholders in publicly held corporations: An exploratory analysis. Journal of Financial Economics, 20; 317-40. Healy, P.M., and J.M. Wahlen, 1998. A review of the earnings management literature and its implications for standard setting. Accounting Horizons 13 (4):365-383. Huang, Henry, 2004. Shareholder Rights and the Cost of Equity Capital. Working Paper, http://papers.ssrn.com/sol3/papers.cfm?abstract_id= 594505,1-32. Holderness, C.G., dan Sheehan, D.P. 1988. The role of majority shareholders in publicly held corporations: An exploratory analysis. Journal of Financial Economics, 20: 317-40. Jensen, M. C., and W.H. Meckling, 1976. Theory of the Firm: Managerial Behavior, Agency Costs and Ownership Structure. Journal of Financial Economics, Vol. 3, No. 4, October: 305-360. La Porta, Rafael, F. Lpoez-De-Silanes, and A. Shleifer, 1999. Corporate Ownership Around the Word. Journal of Finance, Vol. 54, No. 2: 471-517. Li, Ching Chun.1975. Path Analysis: A Primer. Pacific Grove, CA: Boxwood Press. Murni, 2003, “Pengaruh Luas Ungkapan Sukarela dan Asimetri Informasi terhadap Cost of Equity Capital pada Perusahaan Publik di Indonesia”, Simposium Nasional Akuntansi VI. Mutia, Triska. 2011. Pengaruh Budaya Organisasi Terhadap Sistem Pengendalian Manajemen Dalam Upaya Meningkatkan Penerapan Prinsip-Prinsip Good Corporate Governance Serta Dampaknya Terhadap Kinerja Manajerial (Studi Empiris Pada Perusahaan BUMN di Kota Banda Aceh). Thesis program magister ilmu akuntansi Unsyiah. Mardiyah, A.A., 2002. Pengaruh Informasi Asimetri dan Disclosure terhadap Cost of Equity Capital. Jurnal Riset Akuntansi Indonesia, Vol. 5, No. 2, Mei: 229-256. Modigliani, F., and M.H. Miller, 1958. The Cost of Equity, Corporate Finance, and the Theory of Investment. American Economics Review, Volume XLVIII, Number Three, June: 261-297. Navissi, F., dan Naiker, V. 2006. Institutional ownership and corporate value. Managerial Finance, 32 (3): 247-56. Ohlson, J. 1995 “Earning, Book Value, And Devidens In Equity Valuation”, Contempory Accounting Research, Vol 11: 661-687. Pramono, Doni. 2006. Pengaruh Asimetri Informasi dan Kualitas Informasi terhadap Cost of Equity Capital.Thesis, Universitas Airlangga Surabaya. Sekaran, Uma.2000.Research Method for Business.New York: Jhon Willey & Sons, Inc. Shleifer, A., and R. W. Vishny, 1997. A Survey of Corporate Governance. Journal of Finance, Vol. LII, No. 2, June: 737-783. Sukartha, I Made, 2004. Pengaruh Manajemen laba dan Kepemilikan Manajerial pada Kesejahteraan Pemegang Saham Perusahaan Target Akuisisi. Jurnal Eknomi Fakultas Ekonomi, Universitas Udayana. Sari, Kumala, Reza. 2005. Faktor-faktor yang Berpengaruh terhadap Nilai Perusahaan dengan Investasi sebagai Variabel Moderating, Thesis, program magister manajemen, Universitas Diponegoro Semarang. Tarjo. 2006. Pengaruh Konsentrasi Kepemilikan Institusional dan Leverage terhadap Manajemen Laba, Nilai Pemegang Saham serta Cost of Equity Capital. Simposium Nasional Akuntansi XI Pontianak. The National Conference UKWMS Surabaya, Pengaruh Kepemilikan Institusional Teradap Nilai Perusahaan: Sebuah Tinjauan Hubungan Non Linier (Studi Empiris Pada Perusahaan di Bursa Efek Indonesia). Utami, Wiwik 2005. Pengaruh Manajemen Laba Terhadap Biaya Modal Ekuitas (Studi pada Perusahaan Publik Sektor Manufaaktur)”. Simposium Nasional Akuntansi VII, Solo. Weston, J. Fred, and Thomas E. Copeland, 1996. Managerial Finance, 9th Ed, Los Angeles: The Dryden Press.